Sugar Sweetened Beverages (SSBs)-Awareness, Intention and Self-Efficacy Among Low-Income Adults in a Tertiary Care Setting - Mohsin, Shamaila; Zahoor, Mamoona; Mashhadi, Syed Fawad; Saleem, Noman; Ansari, Waleed; Akhtar, Samreen; Inam, Ayesha; Ahmed, Smaak; Karim, Asad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the awareness, self-efficacy and intention of Sugar Sweetened Beverages (SSBs) among low-income staff members of a tertiary care hospital.Study Design: Cross sectional analytic study.Place and Duration of Study: Tertiary care hospital in Rawalpindi Pakistan, for 4 months, from May to Aug 2022.Methodology: The research was conducted among low-income urban adults of a tertiary care hospital in Rawalpindi Pakistan.A non-probability purposive sampling technique was used to select a sample of 200 participants. After taking informed consent the data was collected using a validated questionnaire to assess the SSB-related awareness, self-efficacy and intention.The association between SSB-related constructs and demographic factors was analyzed by using chi-square test and a p-valueof ≤ 0.05 was considered as significant.Results: The mean age of the participants was 21(SD=2.9). Majority 124(62%) of the participants were male, while almost two third 150(75%) had a higher secondary education. Remarkably participants had good SSBs related awareness 170(85%), selfefficacy 151(75.5%) and intention 177(88.5%). Whereas 60(30%) of the participants rarely using sugary drinks, comprised of 35(58.3%) females and 25(41.7%) males. However, association between these two variables was statistically significant (p=0.001). Association analysis between sociodemographic with SSB-related constructs, reported significant association between awareness with employment status (p-value=0.05) and self-rated health status (p-value=0.001). Conclusion: The current study concluded that despite less education level and monthly income. Majority of the participants consumed sugary drinks once weekly but not daily with good awareness, self-efficacy and intention, whereas no significant association was evident between gender and SSBs related awareness, self-efficacy and intention.